2021
DOI: 10.1016/j.injury.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study of transpedicular vs. extrapedicular approach for kyphoplasty and vertebroplasty in the thoracic spine

Abstract: Introduction: Percutaneous vertebral augmentation is a common therapeutic approach for osteoporotic or osteolytic vertebral fractures. Due to the variable pedicle anatomy two different approaches, the transpedicular and the extrapedicular approach have been established. In particular, in the middle and upper thoracic spine, percutaneous procedures are challenging because of difficult visualisation of anatomical landmarks and a more unfavourable anatomy with smaller and differently orientated pedicles. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…All patients were under local anesthesia, including the skin, subcutaneous tissue, articular synovial joint, and local periosteum at the bony entry point. A 18G puncture needle ( Figure 3A ) was inserted from the skin puncture point with 40° of abduction following the direction of the marker line ( 6 ), and the needle tip was slipped over the supra-articular process, then the needle tip reached the junction of the superior pedicle notch and the vertebrae. Under anterior-posterior ( Figure 3A ) and lateral fluoroscopy views, the tip of the needle is in an ideal position ( Figures 3A,G ), which is the bony entry point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were under local anesthesia, including the skin, subcutaneous tissue, articular synovial joint, and local periosteum at the bony entry point. A 18G puncture needle ( Figure 3A ) was inserted from the skin puncture point with 40° of abduction following the direction of the marker line ( 6 ), and the needle tip was slipped over the supra-articular process, then the needle tip reached the junction of the superior pedicle notch and the vertebrae. Under anterior-posterior ( Figure 3A ) and lateral fluoroscopy views, the tip of the needle is in an ideal position ( Figures 3A,G ), which is the bony entry point.…”
Section: Methodsmentioning
confidence: 99%
“…However, owing to the anatomical characteristics of the pedicle, unilateral puncture does not easily reach the center of the vertebral body, and there is a risk of asymmetric distribution of bone cement, which subsequently results in vertebral biomechanical imbalance and even vertebral refracture ( 5 ). To compensate for this deficiency, it has been suggested that a parallel extra-pedicular approach be used, which has a lower probability of puncture failure and allows bilateral cement dispersion ( 6 , 7 ). However, Liu et al ( 8 ) showed that the lumbar segmental artery is closely related to the trajectory of this approach, and that puncture is prone to segmental artery injury.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [9] , we revealed that, compared to CPA, TPA employed a more lateral puncture entry point, wider and safer range of the puncture transverse angle, and higher success rate. The extrapedicular approach produced a lower risk of entry into the intraspinal, compared to CPA and TPA, and this approach better facilitated entry into the vertebral midline, relative to CPA and TPA, since the entry point of the extrapedicular approach was more lateral than others [10] . However, due to the iliac shielding and the broad size of the L4 and L5 vertebrae, it is very di cult to apply these approaches in these regions [6,9] .…”
Section: Introductionmentioning
confidence: 92%
“…extrapedicular approach is more lateral than CPA and TPA 10 . However, due to iliac shielding and the width of the L4 and L5 vertebrae, it is very difficult to apply these approaches in these regions 6,9 .…”
mentioning
confidence: 93%